Kontradyktoryjność i inkwizycyjność w europejskiej procedurze cywilnej XIX i XX wieku - Stawarska-Rippel, Anna (Czasopismo Prawno-Historyczne, 2018)
Socialisation of private law in the second half of the 19th century brought about a new approach to a civil process and its purpose. The main characteristics of the evolution of the civil procedure in the 19th and 20th centuries was limited autonomy of the parties to a process. This limitation was introduced to ensure fair, expedient and cost-effective judgment. A tendency to replace the principle of an adversarial trial with elements of an inquisitorial trial was observed in civil law as well as common law systems. Relevant changes were fi rst made in the Franz Klein Austrian code of civil procedure, followed by departures from the formal truth in the civil process implemented in the system in Germany, Hungary, the Swiss cantons of Zurich and Bern, in Poland, and later, in the second half of the 20th century, also in France. In the common law system, the reform of 1999 ascertained judges a number of discretionary powers to help them establish the facts in a civil proceeding. Those changes added the public element in the civil procedure, but the very idea of a private process and the protection of private interests has been maintained. The totalitarian regimes which emerged in some European states considerably distorted the process of shaping the relationship between the state and the individual. In the socialist civil proceeding, the principle ne eat iudex ultra petita partium was replaced with ex offi cio ultra petita, which was a novelty characteristic of the civil procedure of totalitarian states. The departure from an adversarial principle in the socialist civil process was not much different from the general tendencies observed in the civil procedure in West European states. After the political transformations and change of the regime, former states of the Eastern Bloc sought to signifi cantly increase the autonomy of the parties in a civil process. However, as experience of the Western European states shows, certain public elements must be taken into account in a civil procedure if the European Convention on Human Rights is to be observed.